2014
DOI: 10.3855/jidc.3676
|View full text |Cite
|
Sign up to set email alerts
|

Molecular typing of Staphylococcus aureus collected from a Major Hospital in Amman, Jordan

Abstract: Introduction: Over the past decade methicillin-resistant Staphylococcus aureus (MRSA) has been recognized as a major cause of healthcare associated infections. Recently, however, epidemiology of this pathogen has changed drastically with the emergence of new clones in the community. Efficient epidemiological typing methods are essential to monitor and limit the occurrence and spread of epidemic clones. Methodology: A total of sixty S. aureus isolates were collected from the Jordan University hospital in Amman-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 29 publications
3
27
2
Order By: Relevance
“…The rest of the antimicrobials for both types of staphylococci showed no significant differences (Figure 3) Susceptibility rates to the other antimicrobials were evaluated among outpatient MRSA isolates, these were 74% for quinolones and 69% TMP/ SMX, respectively. An earlier study carried out in the Jordan University Hospital demonstrated that MRSA susceptibility to quinolones was 15%, clindamycin 68%, and gentamicin 68%,respectively [35]. In the current study, a relatively higher susceptibility rates were observed for quinolones 74%, clindamycin 56%, and gentamycin 94%, respectively.…”
Section: Discussionsupporting
confidence: 50%
“…The rest of the antimicrobials for both types of staphylococci showed no significant differences (Figure 3) Susceptibility rates to the other antimicrobials were evaluated among outpatient MRSA isolates, these were 74% for quinolones and 69% TMP/ SMX, respectively. An earlier study carried out in the Jordan University Hospital demonstrated that MRSA susceptibility to quinolones was 15%, clindamycin 68%, and gentamicin 68%,respectively [35]. In the current study, a relatively higher susceptibility rates were observed for quinolones 74%, clindamycin 56%, and gentamycin 94%, respectively.…”
Section: Discussionsupporting
confidence: 50%
“…MRSA is one of the most commonly isolated pathogen associated with general and nosocomial infections worldwide including Jordan [5,24]. The incidence of MRSA varies by location from one institution to another, and from Country to another.…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcus aureus is one of the most commonly isolated human bacterial pathogen and is responsible for causing a battery of diseases ranging from mild superficial infections such as skin infections to severe life-threatening infections such as, endocarditis, deep-seated abscesses, pneumonia and septicemia [1][2][3][4][5]. The ability of S. aureus to cause a spectrum of diseases both in humans and animals is due to a combination of bacterial virulence factors [6].…”
Section: Introductionmentioning
confidence: 99%
“…In Kuwait, the reported proportions of MRSA-ST80 among MRSA strains were 38 [45]. In Jordan, MRSA-ST80 strains were detected in 34.1% (14/41) of all MRSA strains recovered from infections from 2009 to 2010 [46]. Two studies reported that MRSA-ST80 strains represented 9.8% (4/41) and 5.4% (2/37) of all MRSA strains recovered from nasal and fecal carriage, respectively [47,48].…”
Section: Middle Eastmentioning
confidence: 99%